A comparison of the flexural properties of PLA and ABS printed parts - Sudin, Mohd Nizam; Md Daud, Nazri; Yusuff, Mohd Asri (Penerbit UTeM Press, 2022)
The additive manufacturing (AM) technique produces three-dimensional objects by stacking successive layers of material. Fused deposition modelling, abbreviated FDM for convenience, is an additive manufacturing (AM) technique. Using FDM, objects are created by successively depositing molten filaments of thermoplastic onto the printing surface. This is referred to as slicing. The mechanical properties of FDM-printed parts depend on a number of factors, including the composition of the material, the extrusion temperature, the printing parameters, and the ambient temperature at the time the parts are printed. The objective of this study was to investigate the consistency of mechanical properties of elements produced using FDM additive manufacturing technology. Ten thermoplastic ABS and PLA samples were subjected to flexure testing in order to accomplish this. Utilizing the Instron 5585 Floor Model Testing System, flexure testing was conducted. The ultimate flexural strength, along with the strain and Young modulus, was studied. During flexural tests, the thermoplastic ABS material demonstrated greater consistency in terms of its mechanical properties. The fact that different PLA samples had different flexural strengths showed that their mechanical properties were less repeatable.